Impact of Work Overload Work Stress and Work Discipline on Employee Job Satisfaction - Irma Galuh Septiany; Detak Prapanca; Dewi Komala Sari (Jurnal Pamator)
This research aims to determine the relationship between work overload, work stress, and work discipline in influencing job satisfaction. The study employs a quantitative approach as the research method. The population for this research includes all employees in the Sidoarjo region, totaling 210 employees. A sample of 137 active employees is taken using the simple random sampling technique. The data used in this research consist of primary data obtained through the distribution of questionnaires to respondents. Data analysis is conducted using Partial Least Square (PLS) with the assistance of the SmartPLS program. The results of the research, based on the inner model test calculations, indicate that the variables of work overload, work stress, and work discipline significantly influence job satisfaction